한국어 문법 형식의 의미 기술을 위한 의미의 종류 설정에 대하여 - 박재연 (한국어 의미학, 2022)
This paper aims to distinguish various kinds of meaning types, to point out several problems on the current usage in Korean linguistics, and to propose a desirable way of using these terminologies. Referential meaning and conceptual meaning are two aspects of signifié of language as a sign, semantic meaning and pragmatic meaning are concepts related to the level of meaning production. Basic meaning and extended meaning are distinctions of ‘senses’ that polysemic words can have. Descriptive meaning, expressive meaning and social meaning are the distinctions for ‘semantic components’. I propose that by clarifying these differences, semantic description of grammatical forms can be made more efficient. Even though efforts to find ‘core meaning’ in semantic description of the grammatical forms continued, the relationship between core meaning and secondary meaning has not been clearly presented. Furthermore, I believe that there is more room for debate whether finding this ‘core meaning’ is a necessary task in all the semantic description of grammatical forms.
Keywords: 지시적 의미; 개념적 의미; 의미론적 의미; 화용론적 의미(pragmatic meaning); 기본 의미(basic meaning); 확장 의미; 기술적 의미; 표현적 의미; 사회적 의미; 핵심 의미; 의미 항목; 의미 성분; referential meaning; conceptual meaning; semantic meaning; pragmatic meaning; basic meaning; extended meaning; (descriptive meaning; (expressive meaning; (social meaning; core meaning; sense; semantic component